Just Transition in European Coal Regions: Comparative Analysis of Good Practices under the European Green Deal - Oplotnik, Žan Jan; Peres De Bessa Vilela, Noémia; Kolšek, Vasja; Kolšek, Meta (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The phase-out of coal represents a major structural transformation for coal-dependent regions in the European Union, with significant socio-economic implications for regional labour markets, economic structures, and demographic stability. This study examines the just transition process in selected European coal regions using a comparative case-study methodology. The analysis focuses on four key dimensions of transition performance: governance capacity, labour-market outcomes, economic diversification, and demographic trends. To enhance analytical consistency, the paper introduces a qualitative Just Transition Performance Index (JTPI), which integrates these dimensions into a structured comparative framework. Based on empirical evidence and index-based interpretation, the study develops a typology of coal regions, distinguishing structurally resilient regions, transitional regions with mixed outcomes, and socially vulnerable regions. The findings contribute to the understanding of regional transition dynamics and highlight the importance of institutional capacity, strategic planning, and economic diversification for achieving sustainable and socially balanced transition outcomes.